2015
DOI: 10.15204/jkobgy.2015.28.1.046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trogopterorum Faeces on the Apoptostic Cell Death in Breast Cancer Cells

Abstract: Objectives: This study was designed to investigate the effects of Trogopterorum Faeces on the apoptostic cell death in breast cancer cells.Methods: In the experiment, the effects of Trogopterorum Faeces on proliferation rates and type of cell death were investigated using MCF-7 cells in vitro. The effects on expression levels of caspase 3 and caspase 9 were also investigated.Results: The effects on expression levels of caspase 3 and caspase 9 were also investigated. In the present results, treatment with Trogo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Currently, several compounds isolated from Wu-Ling-Zhi, such as 3- O -α- l -(2″ E ,4″ E -di- p -coumaroyl)-rhamnoside, bis(7-hydroxyheptyl) decanedioate and bis(7-hydroxyheptyl) octanedioate, were found to have significant antithrombin activity [14, 17]. Besides, a recent study showed that Wu-Ling-Zhi could trigger caspase dependent apoptosis in breast cancer cells (MCF-7 cells) [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, several compounds isolated from Wu-Ling-Zhi, such as 3- O -α- l -(2″ E ,4″ E -di- p -coumaroyl)-rhamnoside, bis(7-hydroxyheptyl) decanedioate and bis(7-hydroxyheptyl) octanedioate, were found to have significant antithrombin activity [14, 17]. Besides, a recent study showed that Wu-Ling-Zhi could trigger caspase dependent apoptosis in breast cancer cells (MCF-7 cells) [29].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, a recent study showed that Wu-Ling-Zhi could trigger caspase dependent apoptosis in breast cancer cells (MCF-7 cells) [29].…”
Section: Resultsmentioning
confidence: 99%
“…또한 최 근 발표된 연구에 따르면 유방암치료에 있어서 통 합의학 즉, 서양의학적 치료와 한의학적 치료를 함 께 시행했을 때 수술, 화학요법 및 방사선요법의 부작용을 감소시켜 치료율을 높일 수 있음이 확인 되었다. 또 생존기간의 연장과 삶의 질도 향상시키 는 효과를 보여, 앞으로의 유방암 치료에 대한 새 로운 접근법을 제시하였다 11 ① decrease in cell viability (100, 300, 600 μg/mL) ② decrease of Bcl-2 (300, 600 μg/mL) ③ increase of Bax protein (300, 600 μg/mL) ④ induction of caspase-3 activation (100, 300, 600 μg/mL) ⑤ no effect on induction of caspase-8, 9 activation ⑥ increase in the level of p21 ⑦ no effect on increase in p53 expression ⑧ increase of RIP-1 expression (300, 600 μg/mL) ⑨ no effect on Survivin expression 34,35,[37][38][39]42,43,46,50,52,[54][55][56][57][58]65…”
unclassified